Effect of nonstoichiometry on elastic properties of niobium carbide NbCy. (February 2021) - Valeeva, Albina A.; Gusev, Aleksandr I.
Abstract: The investigation of structure of coarse-crystalline powders of nonstoichiometric niobium carbide NbC y have shown that the particles of these powders are monocrystalline and possesses anisotropy of elastic properties. The changes of elastic constants c ij in the homogeneity interval from NbC0.70 to NbC1.00 of nonstoichiometric niobium carbide are evaluated for the first time. It is found that the elastic stiffness constants c ij of a disordered NbC y decrease as the niobium carbide composition deviates from stoichiometry. The lowest and almost independent of the direction ( hkl ) values of G hkl for NbC y are observed in the (111) plane. The isotropic bulk, shear and Young's moduli of nonstoichiometric NbC y niobium carbide which are derived from its elastic constants c ij corresponds to the generalized experimental literature data. It is established that the deviation of niobium carbide composition from stoichiometry is accompanied by decrease of the elastic anisotropy. Graphical abstract: Unlabelled Image Highlights: Powder particles of nonstoichiometric niobium carbide NbC y are monocrystalline. Micro- and nanoparticles of a disordered NbC y possesses anisotropy of elastic properties. Elastic properties of NbC y decrease as its composition deviates from stoichiometry. A deviation of NbC y from stoichiometry leads to decrease of the elastic anisotropy.